Acne and diet: a review. (22nd August 2021) - Conforti, Claudio; Agozzino, Marina; Emendato, Giovanni; Fai, Annatonia; Fichera, Federica; Marangi, Giovanni F.; Neagu, Nicoleta; Pellacani, Giovanni; Persichetti, Paolo; Segreto, Francesco; Zalaudek, Iris; Dianzani, Caterina
Abstract: Acne is one of the most frequent dermatological afflictions especially for people in their first 30 years of age. Several studies have shown that nutrition is one of the key factors involved in acne pathogenesis. Data show that a high glycemic index diet may be a trigger in acne pathogenesis, while patients with a low glycemic index diet have fewer acne lesions. Milk and chocolate are also involved in the exacerbation of acne. However, foods rich in omega‐3 fatty acids suppress the production of inflammatory cytokines with therapeutic effect. Additionally, docosapentaenoic acid and γ‐linolenic acid have demonstrated improved acne lesions. The aim of this review was to summarize current knowledge on the association between acne and diet with special attention to the most frequently discussed factors involved in its pathogenesis: milk, chocolate, omega‐3 fatty acids, hyperglycemia, hyperinsulinism, and IGF‐1.